2017
DOI: 10.1063/1.4973371
|View full text |Cite
|
Sign up to set email alerts
|

Impact of N-plasma and Ga-irradiation on MoS2 layer in molecular beam epitaxy

Abstract: Recent interest in two-dimensional materials has resulted in ultra-thin devices based on the transfer of transition metal dichalcogenides (TMDs) onto other TMDs or III-nitride materials. In this investigation, we realized p-type monolayer (ML) MoS2, and intrinsic GaN/p-type MoS2 heterojunction by the GaN overgrowth on ML-MoS2/c-sapphire using the plasma-assisted molecular beam epitaxy. A systematic nitrogen plasma (N2*) and gallium (Ga) irradiation studies are employed to understand the individual effect on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…43 However, our previous reports show the enormous quenching (100-150 times) of PL for nitrogen plasma irradiated MoS 2 layers and 2D/3D heterojunctions. 16,23 In this study, we preserved the PL signal of the QW with relatively high intensity (quenched by 5 times) and a comparable peak width of 70 meV by using the low nitrogen flow rate and low forward power of plasma source for the growth of In 0. 15 The blue shift in PL spectra with respect to the MoS 2 single layer confirmed that the MoS 2 well exhibits the quantum confinement effect.…”
Section: -mentioning
confidence: 91%
“…43 However, our previous reports show the enormous quenching (100-150 times) of PL for nitrogen plasma irradiated MoS 2 layers and 2D/3D heterojunctions. 16,23 In this study, we preserved the PL signal of the QW with relatively high intensity (quenched by 5 times) and a comparable peak width of 70 meV by using the low nitrogen flow rate and low forward power of plasma source for the growth of In 0. 15 The blue shift in PL spectra with respect to the MoS 2 single layer confirmed that the MoS 2 well exhibits the quantum confinement effect.…”
Section: -mentioning
confidence: 91%
“…Raman spectraof pristine and N * 2 -irradiated MoS 2 mono-layers [98]. Reprinted from Reference [98], with the permission of AIP Publishing. Figure 23 and the inset, the PL intensity increased with increasing plasma irradiation time.…”
Section: Plasma Irradiationmentioning
confidence: 99%
“…For instance, thermal annealing induces intermediate defect states while the thermodynamically non-equilibrium growth processes result in unintentional defects [10,12]. Due to the Li intercalation and the exposure of high energetic N-plasma radicals to the MoS 2 layer, a structural phase change from the thermodynamically most favorable form of trigonal prismatic 2H-MoS 2 to a metastable octahedral 1T-MoS 2 takes place which results in an enormous quenching of photoluminescence intensity [7,13,14]. In contrast, the intrinsic and extrinsic point defects significantly enhance the PL intensity of 2D single layer MoS 2 owing to the stronger interaction of excitons with the localized states [10,11].…”
Section: Introductionmentioning
confidence: 99%